INDICATORS OF CELLULAR AND HUMORAL IMMUNITY IN CHRONIC OBSTRUCTIVE PULMONARY DISEASE IN CHILDREN (Web of Medicine: Journal of Medicine, Practice and Nursing, 2024)
Chronic obstructive pulmonary disease is a common lung disease that is accompanied by cough, sometimes with sputum, difficulty breathing, wheezing and fatigue. In the development of chronic obstructive pulmonary disease in children, the premorbid background and the state of general reactivity of the body play an important role. The aim of the study was to study the state of immunity in children with chronic obstructive pulmonary disease. We examined 100 children who were inpatients in the children's department of the clinic of SamMI No. 1 from 2011-2018. Group I consisted of 30 patients aged 3-7 years, group II - 70 patients aged 8-15 years. The studies confirm the significant pathogenetic significance of immunological deficiency on the course of chronic obstructive pulmonary disease in children and indicate the need for its correction.